Umbelliprenin via increase in the MECP2 and attenuation of oxidative stress mitigates the autistic-like behaviors in mouse model of maternal separation stress - Karimi, Parnian; Ghahfarroki, Mehryar Shahgholian; Lorigooini, Zahra; Shahrani, Mehrdad; Amini-Khoei, Hossein (Frontiers in Pharmacology, 2024)
Introduction: Autism spectrum disorder (ASD) is a complex neurodevelopmental condition. Maternal separation (MS) stress is an early-life stress factor associated with behaviors resembling Autism. Both MECP2 and oxidative stress are implicated in the pathophysiology of Autism. Umbelliprenin (UMB) is a coumarin compound with various pharmacological properties. Our study aimed to investigate the potential effects of UMB in mitigating autistic-like behaviors in a mouse model subjected to MS stress, focusing on probable alterations in MECP2 gene expression in the hippocampus. Methods: MS paradigm was performed, and mice were treated with saline or UMB. Behavioral tests consisting of the three-chamber test (evaluating social interaction), shuttle box (assessing passive avoidance memory), elevated plus-maze (measuring anxiety-like behaviors), and marble-burying test (evaluating repetitive behaviors) were conducted. Gene expression of MECP2 and measurements of total antioxidant capacity (TAC), nitrite level, and malondialdehyde (MDA) level were assessed in the hippocampus. Results: The findings demonstrated that MS-induced behaviors resembling Autism, accompanied by decreased MECP2 gene expression, elevated nitrite, MDA levels, and reduced TAC in the hippocampus. UMB mitigated these autistic-like behaviors induced by MS and attenuated the adverse effects of MS on oxidative stress and MECP2 gene expression in the hippocampus. Conclusion: In conclusion, UMB likely attenuated autistic-like behaviors caused by MS stress, probably, through the reduction of oxidative stress and an increase in MECP2 gene expression.